Evaluating the financial protection of patients with chronic disease by health insurance in rural China - Sun, Qiang (BioMed Central, 2009)
BACKGROUND: A growing number of developing countries are developing health insurance schemes that aim to protect households, particularly the poor, from financial catastrophe and impoverishment caused by unaffordable medical care. This paper investigates the extent to which patients suffering from chronic disease in rural China face catastrophic expenditure on healthcare, and how far the New Co-operative Medical Insurance Scheme (NCMS) offers them financial protection against this. METHODS: A household survey was conducted in six counties in Ningxia Autonomous Region and Shandong Province, with a total of 6,147 rural households, including 3944 individual chronic disease patients. Structured questionnaires were used with chronic disease patients to investigate: their basic social and economic characteristics, including income and expenditure levels and NCMS membership; and their health care utilization, associated healthcare costs and levels of reimbursement by NCMS. 'Catastrophic' expenditure was defined as healthcare expenditure of more than 40% of household non-food expenditure. RESULTS: Expenditure for chronic diseases accounted for an average of 27% of annual non-food per capita expenditure amongst NCMS members in Shandong and 35% in Ningxia. 14-15% of families in both provinces spent more than 40% of their non-food expenditure on chronic healthcare costs. Between 8 and 11% of non NCMS members and 13% of NCMS members did not seek any medical care for chronic illness. A greater proportion of NCMS members in the poorest quintile faced catastrophic expenditure as compared to those in the richest quintile in both study sites. A slightly higher proportion of non-NCMS members than NCMS member households faced catastrophic expenditure, but the difference was not statistically significant. CONCLUSION: A significant proportion of patients with chronic diseases face catastrophic healthcare costs and these are especially heavy for the poor. The NCMS offers only a limited degree of financial protection. The heavy financial burden of healthcare for chronic disease poses an urgent challenge to the NCMS. There is an urgent need for a clear policy on how to offer financial protection to those with chronic disease.